The Usage of Cohesive Devices During Text Translation from Albanian to English and Vice Versa - Vula, Elsa (European Journal of Social Science Education and Research, 2022)
Translation as a complicated process requires a great commitment and hard work in order to realize the text transformation in the best coherent and meaningful way. It is generally known, that no two languages in world have more similarities than differences in their construction. Because of high number of differences that they may share, problems or challenges in the process of translation increase. This research paper focuses on the usage of cohesive devices during text translation from Albanian to English and vice versa. Firstly, this paper introduces the theoretical background on translation, text linguistics and the internal part of a text. Secondly, it elaborates the importance of cohesion and coherence, as criteria of text linguistics as well as their role in the process of translation. In this research has been used the empirical method, in analyzing the texts translation from Albanian to English, by elaborating the addition of cohesive devices which enabled a coherent translation. In addition, there is presented a text translation from English to Albanian, which shows the non-coherent translation and coherent because of the differences among Albanian and English due to linguistic relativism, demonstrative pronouns and noun’s cases.